Implementation of E-book based on 3D Pageflip Professional to Improve Conceptual Understanding of Science for Elementary School Students - ARIF FUDIN; RISTIANA DYAH PURWANDARI (Universitas Muhammadiyah Purwokerto, 2021)
This study aims to determine the benefits of using e-book teaching materials as an alternative to improve conceptual understanding of science for Elementary School students. Students who have an understanding will be able to explain again the lessons they have learned based on their understanding so that learning will be meaningful. The method in this research is the literature study method. The type of this data is secondary data. The method in this research is literature study method. The data obtained were collected, analyzed, and concluded to get conclusions about the literature study. Based on the research results, literature studies from several research results and journal articles show that the benefit of e-book can improve conceptual understanding of science for Elementary School students.